Understanding Selfies - Katarzyna Pisanski (Frontiers Research Topics, 2018)
In the year 2013, 'selfie' was named word of the year by Oxford Dictionaries in recognition of dramatic changes in frequency, prominence, and register of the term. This drastic increase in selfie-taking was spurred by two factors. The first was the advent of smartphones equipped with front cameras and preview screens that made it easy to compose a photographic self-portrait by a process of deliberately exploring one's image, choosing a pose, and finally taking the picture. The second key change contributing to the rise of the selfie age was the increasing availability of internet connections. It is estimated that about 50% of the world population has access to the internet today (2018; https://www.internetworldstats.com). At the end of the past century, this percentage was a mere 1%. The growth of the internet infrastructure simultaneously spurred the development of social network applications such as Facebook, Twitter, Snapchat, and Instagram, providing accessible media for sharing photographs including photographic self-portraits. However, despite their tremendous reach and popularity, selfies have so far received relatively little attention by the scientific community, especially within psychology. Thus, we proposed a Frontiers in Psychology Research Topic to expand empirical and theoretical work on the massively popular, yet scientifically unexplored, phenomenon of the selfie. The articles published in this eBook offer a multifaceted insight into current scholarly work on this topic.